A Group-Based Walking Study to Enhance Physical Activity Among Older Adults: The Role of Social Engagement. (October 2021) - Liu, Yujun; Lachman, Margie E.
Objectives: The aim of this study was to explore social engagement and social comparisons as mechanisms to increase physical activity among older adults. Methods: Participants (N = 60, mean age = 65.7) were randomly assigned to one of two conditions. Participants in the treatment condition used the application to track their daily walking steps and interact via text messages with their group members for 4 weeks. Participants in the control group used the application only to track their own walking steps. Outcome variables included mean weekly steps, exercise self-efficacy, and social engagement. Results: The results revealed that participants in the experimental condition significantly increased their mean weekly steps and social engagement from the pretest to the posttest whereas the control group did not. These effects were maintained at the 1-month follow up. Discussion: The study expands our understanding of the motivational role of social engagement and social comparison in increasing PA among older adults.